High-Risk Human Papillomaviruses and Breast Cancer in Thi-Qar province/South Iraq - Jabbar Hamad, Bushra; Badi Salih, Manal (University of Thi-Qar Journal of Science, 2019)
The breast cancer is considered one of the most common types of cancer in Iraq, and in Thi-Qar the infections are increasing annually, it constitutes one-third of all cancer types. The HPVs are highly contagious viruses. The important aspect about HPV infections is their relationship with breast cancer. The HPV has a well-known relationship with other neoplasms in other anatomic sites and may have a role in the development of breast cancer. The HPV 16 and 18, are high-risk oncogenic viruses, and they are the most common types that can be detected in malignant tumors. To confirm the role of papillomavirus in the occurrence of breast cancer and because the absence of a study to identify the HPV genotypes in Thi-Qar province, that is necessary to determine the type of vaccine in the future, therefore, this study was conducted. The conventional PCR technique was implemented to detect the presence of HPV DNA in malignant and benign breast tissue, and the real-time PCR used to determinant HPV genotypes. This study was conducted on 100 formalin-fixed paraffin-embedded divided to 80 samples with malignant breast tumors and 20 samples of benign breast tumor were considered as a control group. The results showed that 37 (37%) of samples divided as: 32 (40%) from malignant tumors, and 5 (25%) from benign tumors gave positive results for HPV with significant differences (p<0.05), and the genotype results showed, that the HPV16 is the dominant high-risk genotype in malignant and benign tumors by positive percentage as 35.